2015
DOI: 10.1007/s10803-015-2427-4
|View full text |Cite
|
Sign up to set email alerts
|

The “Reading the Mind in the Eyes” Test: Investigation of Psychometric Properties and Test–Retest Reliability of the Persian Version

Abstract: The psychometric properties of the Persian "Reading the Mind in the Eyes" test were investigated, so were the predictions from the Empathizing-Systemizing theory of psychological sex differences. Adults aged 16-69 years old (N = 545, female = 51.7 %) completed the test online. The analysis of items showed them to be generally acceptable. Test-retest reliability, as measured by Intra-class correlation coefficient, was 0.735 with a 95 % CI of (0.514, 0.855). The percentage of agreement for each item in the test-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 49 publications
10
59
1
Order By: Relevance
“…The Persian version of the RMET translated and explored by Khorashad (2013) and Khorashad et al (2014) was consulted to translate the English RMET into Persian by employing schema theory (Khodadady, 2000a(Khodadady, , 2008a(Khodadady, , 2008bLagzian, 2013) and the guidelines offered for developing multiple choice item tests (e.g., Farhady, Jafarpoor, & Birjandi, 1994; Haladyna, 1994; Khodadady, 1999Khodadady, , 2000b. First, from the section dealing with word definitions, extraneous words not given as the keyed mental state or foils were removed to reduce the number of defined words from 93 to 74.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Persian version of the RMET translated and explored by Khorashad (2013) and Khorashad et al (2014) was consulted to translate the English RMET into Persian by employing schema theory (Khodadady, 2000a(Khodadady, , 2008a(Khodadady, , 2008bLagzian, 2013) and the guidelines offered for developing multiple choice item tests (e.g., Farhady, Jafarpoor, & Birjandi, 1994; Haladyna, 1994; Khodadady, 1999Khodadady, , 2000b. First, from the section dealing with word definitions, extraneous words not given as the keyed mental state or foils were removed to reduce the number of defined words from 93 to 74.…”
Section: Methodsmentioning
confidence: 99%
“…It is based on the assumption that people interact by identifying each others' mental states. According to BWHR&P, the theory is variously referred to as "mentalizing" (Morton, Frith & Leslie, 1991), "mind reading" (Whiten, 1991) K&N administered the Persian RMET validated by Khorashad et al (2014) with the cloze multiple choice item test (CMCIT) designed by Hale et al (1988) as a measure of English language proficiency to 181 undergraduate university students of ELL and Theology and obtained a significant correlation between the two (r = .27, p<.01), indicating that there is a positive relationship between social intelligence and English language proficiency. No study has, however, explored the relationship between social intelligence as measured by the RMET and emotional intelligence as measured by the EQS so far.…”
Section: B Social Intelligencementioning
confidence: 99%
See 2 more Smart Citations
“…Researchers reported an acceptable validity and good stability for RMET. Khorashad, BaronCohen, Roshan et al [23] and Prevost, Carrier, Chowne et al [24], for examples, reported a good validity for the test in samples from different countries.…”
Section: Sessionmentioning
confidence: 99%